Zapletenost vzglasja zloga v slovenskem jeziku - Unuk, Drago (Jezikoslovni zapiski, 2022)
This article presents the profile of two-element obstruent onset clusters in Slovenian in terms of how they match the distribution of sonority, phonological explanations of the manifestation of sonority, and the connection of sonority with the pronunciation, structure, and perception of the syllable. The principle of sonority and the principle of distribution of segments operate in syllable formation. The stimulation perception threshold and Fibonacci sequence are important in observing the difference in sonority increase in individual configurations of segments: they act as a measure for the fricative and stop (FS) configuration to be realized as a regular sequence in syllable onset.
Keywords: Fibonacci sequence; Fibonaccijevo zaporedje; onset; prag zaznave vzbujanja; slovenščina; sonority; stimulation perception threshold; syllable; vzglasje; zlog; zvočnost